Stuitability of Injana Clay For Filling Materials In Earth Fill Dams In Sharqat Distric/ Salah Alden North Iraq. - LOAI MOUSSA RAWEE. (Tikrit Journal of Pure Science)
The Study Aims To Study The Suitability of Injana Clays In North East Sharqat Governorate For Filling Materials In Earth Fill Dams. Three Stations Were Chosed Which Reflect The Study Area.